Contact sensitization to fragrance mix I and fragrance mix II among European dermatitis patients: A systematic review - Botvid, Sofia; Bennike, Niels H.; Simonsen, Anne Birgitte; Johansen, Jeanne Duus; Uter, Wolfgang (Contact Dermatitis, 2024)
Background: Fragrance substances are a frequent cause of contact allergy worldwide. Fragrance exposure varies by sex, age and possibly country, influenced by cosmetic availability, environmental conditions and cultural practices. Objectives: To systematically review and gather prevalence of sensitization to fragrance mix I (FM I) and fragrance mix II (FM II) in consecutively patch-tested European dermatitis patients. Method: A total of 4134 publications on patch test results of European dermatitis patients, published from 1981 to 2022, were systematically reviewed according to a previously registered and published PROSPERO protocol. Results: Eighty-four eligible original articles were analysed. Overall prevalence of sensitization to fragrance mix I (FM I) was 6.81% (95% CI: 6.37–7.28), and FM II was 3.64% (95% CI: 3.3–4.01). Sensitization to FM I was most prevalent in Central and Eastern Europe and to FM II in Western Europe. No clear time trends were observed. Among paediatric dermatitis patients, sensitization prevalence for FM I and FM II was 4.09% (95% CI: 3.37–4.96) and 2.17% (95% CI: 1.53–3.07). Conclusion: The frequency of positive patch test results for both FMI and FMII remains high. Sensitization is also prevalent among children. Enhanced regulation and labelling of cosmetic products play a vital role in averting exposure and sensitization to fragrance allergens.
CRIS-Team Scopus Importer:2024-07-12
Keywords: contact allergy; contact dermatitis; epidemiology; fragrances; patch test